Pendampingan Digitalisasi UMKM: Optimalisasi Aplikasi Takeapp Untuk Meningkatkan Pemasaran Penjualan - Triadinda, Dexi; Yani, Dini; Rosmawati, Ery (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This community service program aims to foster the development of MSMEs in Sirnabaya Village, Karawang Regency, through the utilization of digital technology. The initiative focused on providing mentorship in the use of TakeApp as a simple and effective online marketing tool. The partner involved in this program was Mrs. Sri, the owner of a home based “nasi kuning” business established in 2022. The activity commenced with a Focus Group Discussion (FGD) at Hall 1 of Karawang University of Public Works, organized by the Management Study Program, to identify the needs of MSMEs. This was followed by a hands-on coaching clinic designed to enable business owners to create accounts and operate the application independently. The mentoring program resulted in improved understanding and digital skills among MSMEs, equipping them to develop new, broader, and more efficient marketing channels suitable for home-based businesses. This activity is expected to enhance MSME competitiveness, expand market reach, and promote technology-driven local economic growth.